2013
DOI: 10.1186/1471-2458-13-616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parenting practices on sexual risk-taking among young people in Cameroon

Abstract: BackgroundThere is scanty evidence regarding the impact of parenting practices on young people’s sexual risk-taking in sub-Saharan Africa. Moreover, the extent to which such practices have enduring consequences on adolescents and young adults is little documented. This study uses repeated measures of parent–child relationships, parental monitoring, and parent–child communication about sexual matters to shed some light in these two areas.MethodsThe analysis is based on time-dependent retrospective data on paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…Studies ranged in sample size from 30 to 31 098 and were conducted in 13 SSA countries, with most conducted in Kenya, Ghana and South Africa. Some drew on large-scale national studies including: ‘Transition to Adulthood’ (TTA)47–49 and the ‘Cameroon Family and Health Surveys’ (CFHS) 50 51. Other studies reported findings from more than one SSA country 52–54.…”
Section: Resultsmentioning
confidence: 99%
“…Studies ranged in sample size from 30 to 31 098 and were conducted in 13 SSA countries, with most conducted in Kenya, Ghana and South Africa. Some drew on large-scale national studies including: ‘Transition to Adulthood’ (TTA)47–49 and the ‘Cameroon Family and Health Surveys’ (CFHS) 50 51. Other studies reported findings from more than one SSA country 52–54.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the quality of child-family relationships produced mixed results. One study found that good parent-child relationships (defined as the amount of communication, warmth, love and closeness between mother and child) are protective against multiple partnerships amongst males and females [53] compared to other studies who reported no relationship between parent-child relationships and the number of sexual partners [54]. This finding implies that although family structure is important in reducing the engagement of youth in at-risk behavior, the involvement of parents in the activities of youth and monitoring of these activities are more important.…”
Section: Discussionmentioning
confidence: 99%
“…In some, family structure was classified under living arrangement and this included living alone, with both parents, a single parent or relatives [50]. In another study, family structure included biological parents, biological mother only, biological father only, other relatives and uncorrelated residents [53]. Other studies included grandparents and other relatives as part of the family structure such as an aunt or uncle [48].…”
Section: Family Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Hubungan yang terjalin dengan baik antara orangtua-anak akan melindungi anak dari perilaku seksual sejak dini (Sidze & Defo, 2013). Hal tersebut dapat terjadi karena hubungan orangtua -anak memiliki keterkaitan dengan perilaku seksual seperti keputusan untuk menunda atau mengurangi perilaku seksual (Scony, Deptula, & Henry, 2010;Miller, 2002).…”
Section: Pendahuluanunclassified